ANALISA MEDIA SIBER ZINETFLIX SEBAGAI MEDIA ALTERNATIF TENTANG FILM DI ERA DIGITAL - Idhar Resmadi (Fakultas Seni Rupa dan Desain ITB, 2021)
Nowadays, social media is used to build not only friendship networking but also business. Various companiesand media institutions use social media to disseminate information. One of the most popular social media widelyused by business companies and media institutions is Instagram, including Netflix Indonesia, which has created amass media-based Instagram “Zinetflix”. Zines is considered an alternative media that provides a lot of informationoutside the mainstream mass media channels. The characteristics of zines are community-based, anti-mainstream,and offering a more experimental format than conventional media. Zinetflix is a media innovation in the cyber mediabecause it utilizes various features and technology to become a channel of information. This study uses a qualitativeresearch method with a case study approach. The case study selected is “Zinetflix” which was designed by moviecontent provider Netflix. The data collection was conducted through observations, interviews, and literature studies.The results discussed in this research is how the use of Instagram social media features become an informationmedia space in the cyber media era as Zinetflix does in the celebration of the National Film Day every year.